A New Method For Preparation of Microencapsulated Phase Change Materials (PCMs) For Low Coast Energy in Cooling of Building - mohammed, H.S.; Abbas, S.M.; Mohammed, S.S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Microencapsulated of paraffin wax which acts as core material of phase change material covered by polymer was prepared by using rabid (physical-chemical) with lower energy (green) method. Prepolymer of condensed Melamine-Formaldehyde resin, was solidified by heat effect gradually and surrounds the Paraffin wax as microcapsules. The diameter of the prepared capsules was about (170-220) micron which has a proportion with the prepolymer temperature, otherwise the thermal analysis appears as a best value of enthalpy (Î”H) which was (12 J/gm) when the prepolymer temperature was (60ËšC)